2021
DOI: 10.3389/fimmu.2021.635018
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection Induces Psoriatic Arthritis Flares and Enthesis Resident Plasmacytoid Dendritic Cell Type-1 Interferon Inhibition by JAK Antagonism Offer Novel Spondyloarthritis Pathogenesis Insights

Abstract: ObjectiveBacterial and viral infectious triggers are linked to spondyloarthritis (SpA) including psoriatic arthritis (PsA) development, likely via dendritic cell activation. We investigated spinal entheseal plasmacytoid dendritic cells (pDCs) toll-like receptor (TLR)-7 and 9 activation and therapeutic modulation, including JAK inhibition. We also investigated if COVID-19 infection, a potent TLR-7 stimulator triggered PsA flares.MethodsNormal entheseal pDCs were characterized and stimulated with imiquimod and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 27 publications
1
16
0
1
Order By: Relevance
“…Moreover, as described in many studies, SARS-CoV-2 is able to activate in different ways the immune system; in particular, it can induce interleukin-6 (IL-6)-dependent pathways leading to cytokine storm and macrophage activation syndromes; in addition, it might alter interferon signalling in some cases [ 19 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as described in many studies, SARS-CoV-2 is able to activate in different ways the immune system; in particular, it can induce interleukin-6 (IL-6)-dependent pathways leading to cytokine storm and macrophage activation syndromes; in addition, it might alter interferon signalling in some cases [ 19 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying the onset of PsA after COVID-19 in the present case was unclear, but one study reported that oligodeoxynucleotide (ODN)/imiquimod stimulation induced entheseal plasmacytoid dendritic cells (pDCs) related interferon (IFN)-α production via NF-κB signaling, Toll-like receptor signaling, and JAK/STAT signaling pathways ( 21 ). In addition, the Disease Activity Index score for PsA increases following COVID-19 due to the stimulation of Toll-like receptor 7 pathways in patients with PsA ( 21 ).…”
Section: Discussionmentioning
confidence: 93%
“…[ 41 ] Infections have also been associated with flares of psoriatic arthritis and enthesis. [ 42 ] Such findings have also been extrapolated in pediatric patients suffering from psoriasis who experienced disease flares during a mandatory lockdown and had their medication stopped for COVID-related reasons. [ 43 ] Despite these associations, as well as the excellent safety profile of biological agents in psoriasis patients infected with COVID-19,[ 44 45 46 47 48 49 50 51 ] the rate of biological initiation for psoriasis has decreased during the pandemic.…”
Section: Discussionmentioning
confidence: 99%